METODE PEMBELAJARAN QUICK ON THE DRAW UNTUK MENINGKATKAN HASIL BELAJAR SKI KELAS VII MTS ASSUNNIYYAH TAMBARANGAN - Fahrinawati (AL-ULUM | JURNAL PENDIDIKAN DAN PENGAJARAN, 2023)
This research aims to improve student learning outcomes in the History of Islamic Culture subject by using the Quick on The Draw cooperative learning model in class VII A MTs Assunniyyah Tambarangan. This research is Classroom Action Research (PTK) which consists of 2 cycles which each cycle consists of four stages, namely: planning, implementation, observation and reflection. This Classroom Action Research (PTK) used data collection instruments in the form of observation sheets, test questions and documentation. The results of this research showed that the learning outcomes of students in the History of Islamic Culture subject by applying the Quick on The Draw cooperative learning model have increased, as seen from the percentage of classical learning result before implementation is 44% with an average score of 63, after using Quick on The Draw cooperative learning model, classical learning result in cycle I increased to 68% with an average value of 73 and continued to cycle II, experiencing another increase reaching 92% with an average value of 80.6. In this way, the quick on the draw cooperative learning model can improve the learning outcomes of students in the Islamic Cultural History subject.